2015
DOI: 10.1109/tpwrs.2014.2357218
|View full text |Cite
|
Sign up to set email alerts
|

A UFLS Scheme for Small Isolated Power Systems Using Rate-of-Change of Frequency

Abstract: This letter presents a centralized underfrequency load-shedding (UFLS) scheme using the initial rate-of-change of frequency (ROCOF) to decide whether and how much load needs to be shed. The applicability of the centralized UFLS scheme is shown for a Spanish small isolated power system. Index Terms-Frequency stability, load shedding, power system protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…In [26][27][28] adaptive Under Frequency Load-Shedding (UFLS) scheme is proposed, which disconnects predefined loads based on predetermined frequency threshold values. Adaptive UFLS schemes have been further improved by using both frequency and Rate Of Change Of Frequency (ROCOF) in determination of load-shedding requirement [26,29,30]. Nevertheless, ROCOF can differ for system disturbances in PCC and may vary in time due to transition to islanded mode leading to malfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In [26][27][28] adaptive Under Frequency Load-Shedding (UFLS) scheme is proposed, which disconnects predefined loads based on predetermined frequency threshold values. Adaptive UFLS schemes have been further improved by using both frequency and Rate Of Change Of Frequency (ROCOF) in determination of load-shedding requirement [26,29,30]. Nevertheless, ROCOF can differ for system disturbances in PCC and may vary in time due to transition to islanded mode leading to malfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This result will make damages for the suppliers and customers using the system's power. The authors in [5,6] showed methods to estimate the amount load shedding, which based on the frequency reduction, or the rate of change of frequency (ROCOF). The combination of intelligent load shedding methods has also been studied and developed such as Artificial Neural Network (ANN) [7], fuzzy logic algorithms [8], genetic algorithm (GA) [9] or particle swarm optimization (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…This could cause the over load shedding or the insufficient load shedding. The authors in [6], [7] and [8] present a method to estimate the amount load shedding, it is usually based on the frequency reduction, the rate of change of frequency (ROCOF) or swing equation. Intelligent load shedding methods have also been studied and developed such as artificial neural network (ANN) [9][10], fuzzy logic [11], genetic algorithm (GA) [12][13] and particle swarm optimization (PSO) algorithm [14][15].…”
Section: Introductionmentioning
confidence: 99%